VD_FINDINFO Pron / 2012 / 12 vom 10. Januar 2012 - VD Tribunal cantonal (2012)
FRAIS JUDICIAIRES, DÉCISION SUR FRAIS, AVOCAT D'OFFICE, INDEMNITÉEN GÉNÉRAL | 122 al. 1 let. a CPC (CH), 241 al. 2 CPC (CH), 2 al. 1 RAJ